Reliability and Validity of the Thai Version of the Florida Obsessive-Compulsive Inventory - Ratana Saipanish; Thanita Hiranyatheb; Manote Lotrakul (The Scientific World Journal, 2015)
This study aimed to examine the reliability and validity of the Thai version of the FOCI (FOCI-T), which is a brief self-report questionnaire to assess the symptoms and severity of obsessive-compulsive disorder (OCD). Forty-seven OCD patients completed the FOCI-T, the Patient Health Questionnaire (PHQ-9), and the Pictorial Thai Quality of Life (PTQL). They were then interviewed to determine the OCD symptom severity by the Yale-Brown Obsessive-Compulsive Scale-Second Edition (YBOCS-II) and depressive symptoms by the Hamilton Rating Scale for Depression (HAM-D), together with the Global Assessment of Functioning (GAF) and the Clinical Global Impression-Severity Scales (CGI-S). The result showed that the FOCI-T had satisfactory internal consistency reliability on both the Symptom Checklist (KR-20 = 0.86) and the Severity Scale (α=0.92). Regarding validity analyses, the FOCI-T Severity Scale had stronger correlations with the YBOCS-II and CGI-S than the FOCI-T Symptom Checklist. This implied the independence between the FOCI-T Symptom Checklist and the Severity Scale and good concurrent validity of the FOCI-T Severity Scale. Our results suggested that the FOCI-T was found to be a reliable and valid self-report measure to assess obsessive-compulsive symptoms and severity.